Calcium Scoring on CT Coronary Angiography in Hypertensive Patients as a Criterion for the Prediction of Coronary Artery Disease - Tserioti, Eleni; Chana, Harmeet; Salmasi, Abdul-Majeed (Journal of Cardiology and Cardiovascular Medicine, 2024)
Introduction: Hypertension is the strongest independent predictor of Coronary Artery Disease (CAD) identified by Computed tomography of coronary arteries (CTCA). In this study, CTCA-assessed Coronary Calcium Scoring (CCS) was studied in hypertensive subjects referred for CTCA. Methods: After excluding TAVI and graft assessment patients, the individual electronic health records of 410 consecutive patients who underwent CTCA between July and November 2020, were reviewed with a mean age of 58.7 years. Risk factors were recorded including smoking (38%), hyperlipidaemia (33%), positive family history (22%), systemic hypertension (48%), diabetes mellitus (30%), and male gender (46%). Referral criteria, ethnicity, cardiac, and past medical history were recorded. Patients were stratified into four groups according to CAD severity: absent, mild, moderate, and severe disease, as seen on CTCA. The mean CCS for each CAD category was compared between hypertensive and non-hypertensive patients. Mean CCS were further compared according to the number of coronary arteries affected and the severity of CAD in each artery. Results: Out of all CTCA reports, 200 (48.8%) CCS were interpreted in the very low-risk category, 80 (19.5%) low risk, 58 (14.1%) moderate risk, 23 (5.6%) moderately high risk and 49 (12.0%) high risk. A significant difference in mean CCS and CAD severity was observed between mild, moderate, and severe CAD (p = 0.015 and p < 0.001). Comparison of CCS between hypertensives and non-hypertensives, across the four CAD severity categories, revealed a significant difference in mean CCS in the severe CAD category (p = 0.03). There was no significant difference in the CCS between hypertensives with chest pain and hypertensives without chest pain. A higher number of affected coronary arteries was associated with a higher mean CCS and a significant difference in CCS was observed between hypertensive and non-hypertensive subjects for the number of arteries affected. Similar results were observed when comparing mean CCS in moderate-severely affected coronary arteries. Conclusion: Hypertensive patients with a high CCS were associated with a higher incidence of severe CAD independent of the presence of chest pain. These results suggest that the incorporation of CCS in the investigation of CAD on CT angiography may pose a powerful adjunct in proposing an alternative paradigm for the assessment of patients with hypertension, in the progress of coronary artery disease.